Nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst and preparation method and application thereof

By using a carbon-coated iron selenide dual-function catalyst supported by nitrogen-doped carbon nanotubes in zinc-air batteries, the problems of slow oxygen reversible reaction kinetics, high catalyst cost and poor durability of zinc-air batteries are solved, and efficient and stable electrochemical performance is achieved.

CN118645642BActive Publication Date: 2025-03-07JIANGXI NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410681365.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-03-07
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The oxygen reversible reaction kinetics of existing zinc-air batteries are slow, precious metal catalysts are costly and have poor durability, and transition metal selenides are prone to agglomeration and corrosion under strong alkali conditions.

Method used

The carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes is used to reduce agglomeration and corrosion by coating FeSe2NPs through graphite carbon. The N-CNTs conductive network formed in situ promotes charge transfer and provides rich atomically active sites.

Benefits of technology

A stable and efficient oxygen reduction reaction and oxygen precipitation reaction are achieved, which improves the electrochemical performance of zinc air batteries, including high power density, high energy density and good cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645642B_ABST
    Figure CN118645642B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of zinc-air batteries, and specifically relates to a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, and a preparation method and application thereof. Aiming at the problem that transition metal selenides are easy to agglomerate during application and are easily corroded under strong alkaline conditions, the present invention designs a carbon-coated iron selenide bifunctional electrocatalyst supported by nitrogen-doped carbon nanotubes, and the iron selenide is coated with graphite carbon. The graphite carbon shell can effectively reduce the agglomeration of FeSe2NPs and the corrosion of FeSe2NPs in the subsequent catalytic process, and the N-CNTs conductive network formed in situ can promote the rapid transfer of charges, and the strong interaction between the FeSe2NPs core, N atoms and iron atoms provides abundant atomic active sites, so that the obtained catalyst has stable ORR electrocatalytic performance and OER electrocatalytic performance, and is used as a cathode catalyst for zinc-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc-air batteries, and in particular relates to a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, and a preparation method and application thereof. Background Art

[0002] Rechargeable zinc-air batteries are cost-effective and have a high theoretical energy density (1084 Whkg -1 ), environmental friendliness and good safety, it is widely regarded as one of the promising renewable and sustainable electrochemical energy storage systems. However, the reversible oxygen reactions on the air cathode of zinc-air batteries, including the oxygen reduction reaction (ORR) during discharge and the oxygen evolution reaction (OER) during charge, usually have high energy barriers and slow kinetics in the four-electron transfer process. Although noble metal catalysts show high activity in promoting the kinetics of ORR (such as Pt / C) or OER (such as RuO2 or Ir / C), they are severely restricted by factors such as high cost, poor durability and insufficient bifunctionality.

[0003] Transition metal selenides (TMS; M = iron, cobalt, and nickel) have been considered as ideal candidates to replace noble metal ORR or OER electrocatalysts due to their abundant resources, tunable electronic structures, good charge transfer properties, and excellent catalytic activity. However, TMS NPs are prone to aggregation during the preparation and catalytic processes, which greatly reduces their performance in redox reactions (O2 / 2O 2- ) in catalytic activity and durability.

[0004] In order to improve the activity and stability of TMS-based catalysts, several effective strategies have been explored, including heteroatom doping of carbon substrates, morphology design, defect engineering, and heterojunction structure design. Although the catalysts prepared by these strategies show relatively excellent catalytic performance, TMS NPs are usually exposed to strong alkaline media and still face the problem of poor stability and durability in oxidative operating environments. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst and its preparation method and application. In view of the problem that transition metal selenides are easy to agglomerate during application and are easily corroded under strong alkaline conditions, the present invention designs a nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional electrocatalyst, by coating iron selenide with graphite carbon, the graphite carbon shell can effectively reduce the agglomeration of FeSe2NPs and the corrosion of FeSe2NPs in the subsequent catalytic process, and the in-situ formed N-CNTs conductive network can promote the rapid transfer of charges, and the strong interaction between the FeSe2NPs core, N atoms and iron atoms provides abundant atomic active sites, so that the obtained catalyst has stable ORR electrocatalytic performance and OER electrocatalytic performance, and it is used as a cathode catalyst for zinc-air batteries.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0008] Using soluble iron salt and trimesic acid (H3BTC) as raw materials, an iron-based covalent organic framework is generated through a wet chemical reaction at room temperature; the wet chemical method essentially refers to a liquid phase coprecipitation method. At room temperature, soluble iron salt reacts with trimesic acid, and iron ions coordinate with carboxyl groups to self-assemble to form a Fe-BTC metal organic framework, i.e., an iron-based covalent organic metal framework.

[0009] After the iron-based covalent organic framework is mixed with melamine, melamine acts as a carbon source and a nitrogen source in the whole system to ensure the formation of nitrogen-doped carbon nanotubes. After high-temperature calcination, the mixture is first kept at 450-550°C for 2-4 hours in a nitrogen atmosphere, and then pyrolyzed at 700-1000°C for 1-3 hours to obtain iron carbide nanoparticles loaded with nitrogen-doped carbon nanotubes.

[0010] The iron carbide nanoparticles supported by nitrogen-doped carbon nanotubes are mixed with selenium powder, and then subjected to a selenization reaction, in which the electronegativity of the selenium element replaces the carbon element in the iron carbide to form iron selenide, thereby obtaining a nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst.

[0011] Preferably, the mass ratio of the iron-based covalent organic framework to melamine is 1:1-3. The mass ratio of the two affects the physical and chemical properties of the final catalyst, including the pore structure and nitrogen doping content, which will ultimately have a corresponding impact on its catalytic activity. We have also conducted relevant experiments to explore different ratios, and the data can prove that the best effect is achieved at the ratio provided in this application.

[0012] Preferably, the conditions for high-temperature calcination are: in a nitrogen atmosphere, first maintain at 450-500°C for 2-4h. The decomposition temperature of melamine is 354°C, so it is maintained at a temperature higher than this for a period of time to completely decompose the melamine, and then pyrolyzed at 700-1000°C for 1-3h; the pyrolysis temperature will affect the degree of graphitization and defects of the material. Studies have shown that the material prepared at 800°C has the best performance. Time determines whether it is completely carbonized. Generally speaking, carbonization only takes 1h above 700°C, but to ensure that the material is completely carbonized, the best time selected in this application at 800°C is 2h.

[0013] Preferably, the conditions for the selenization reaction are: in an inert atmosphere, nitrogen-doped carbon nanotube-loaded iron carbide nanoparticles are mixed with selenium powder, and then reacted at 300-500°C for 1-3h. Low temperature or short time cannot ensure complete selenization, and high temperature will cause the selenium powder to sublime, resulting in poor selenization effect; and selenization reaction for too long increases energy consumption.

[0014] Preferably, the mass ratio of iron carbide nanoparticles supported by nitrogen-doped carbon nanotubes to selenium powder is 0.2-1:1.

[0015] Preferably, the molar ratio of the iron salt to trimesic acid is 0.2-1.5:1.

[0016] Preferably, the wet chemical reaction method is: dissolving trimesic acid in a NaOH solution to obtain a solution A;

[0017] Dissolve a soluble iron salt in water to obtain solution B;

[0018] Solution B was added dropwise to solution A, and the mixture was stirred until an iron-based covalent organic metal framework (Fe-BTC) was formed.

[0019] Preferably, the pH value of solution A is 9-12, and the pH value of solution B is 1-3; H3BTC has a low solubility in water, and is dissolved in a sodium hydroxide solution, on the one hand to completely dissolve it, and on the other hand to adjust the pH value of the solution, where the pH value affects the preparation of MOF;

[0020] Preferably, the stirring and mixing time is ≥ 12 h.

[0021] The invention also protects the carbon-coated iron selenide bifunctional catalyst loaded with nitrogen-doped carbon nanotubes prepared by the preparation method.

[0022] The present invention also protects the use of a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes in the preparation of a zinc-air battery cathode catalyst. When the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes is used as a zinc-air battery cathode catalyst, it simultaneously promotes oxygen reduction reaction and oxygen evolution reaction.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention rationally designs and prepares a MOF-derived three-dimensional composite material (Fe-Se@N-CNTs) as an efficient bifunctional electrocatalyst, and applies it to the preparation of zinc-air battery cathodes. The Fe-Se@N-CNTs of the present invention can not only form a one-dimensional nitrogen-doped carbon nanotube (N-CNTs) conductive framework in situ, but also obtain graphite carbon-coated FeSe2NPs. This three-dimensional hierarchical structure gives the Fe-Se@N-CNTs hybrid catalyst efficient and stable ORR and OER electrocatalytic performance, wherein the graphite carbon shell can effectively reduce the agglomeration of FeSe2NPs and the corrosion of FeSe2NPs in the subsequent catalytic process; the in-situ formed N-CNTs conductive network can promote the rapid transfer of charges, and the strong interaction between the FeSe2NPs core, N atoms and iron atoms provides abundant atomic active sites. In addition, the rechargeable zinc-air battery constructed with the optimal Fe-Se-2@N-CNTs catalyst as the cathode shows excellent electrochemical performance, including high power density, high energy density, stable voltage output and excellent cycle stability.

[0025] 2. The present invention adopts a carbon encapsulation strategy to improve the long-term stability of the catalytic material. The stable carbon layer with high conductivity can not only promote the transmission of electrons to enter the active site, but also prevent the FeSe2NPs core from directly contacting the electrolyte, thereby achieving good durability. In addition, in the field of catalysis, metal nanoparticles are usually fixed on a conductive carrier, and the electronic structure of the active site of the metal nanocatalyst can be effectively regulated by the strong interaction between the metal and the carrier, which is called metal-carrier interaction in academia. This interaction force is related to the re-hybridization of electron orbits and charge transfer at the metal-carrier interface, which may lead to the formation of new interfacial chemical bonds and the rearrangement of molecular energy levels, thereby affecting the subsequent ORR and OER reaction activity. In this application, due to the strong interfacial electronic interaction and the electron penetration effect of stimulating the inactive carbon surface, the carbon / metal interface can adjust the bonding strength with the catalyst and the carrier. Therefore, coating TMS NPs with highly porous and conductive graphite carbon can not only prevent NPs accumulation, but also improve the interaction between carbon and FeSe2NPs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a synthesis diagram of the Fe-Se@N-CNTs catalyst of the present invention;

[0027] Figure 2In the figure, (a) is a SEM image of the Fe3C@N-CNTs catalyst of Comparative Example 1, (b) is a TEM image of the Fe3C@N-CNTs catalyst of Comparative Example 1; (c) is an enlarged image of (b);

[0028] Figure 3 In the figure, (a) is the SEM of the Fe-Se-2@N-CNTs catalyst of Example 2, (b) is the SEM of the Fe-Se-2@N-CNTs catalyst of Example 2; (c) is an enlarged view of (b);

[0029] Figure 4 XRD diagrams of Fe3C@N-CNTs of Comparative Example 1, Fe-Se-1@N-CNTs of Example 1, Fe-Se-2@N-CNTs of Example 2, and Fe-Se-3@N-CNTs of Example 3;

[0030] Figure 5 The Raman images are of Fe3C@N-CNTs of Comparative Example 1, Fe-Se-1@N-CNTs of Example 1, Fe-Se-2@N-CNTs of Example 2, and Fe-Se-3@N-CNTs of Example 3;

[0031] Figure 6 It is an ORR performance diagram of Fe3C@N-CNTs of comparative example 1, Fe-Se-1@N-CNTs of example 1, Fe-Se-2@N-CNTs of example 2, Fe-Se-3@N-CNTs of example 3, and Pt / C catalyst;

[0032] Figure 7 It is the OER performance diagram of Fe3C@N-CNTs of comparative example 1, Fe-Se-1@N-CNTs of example 1, Fe-Se-2@N-CNTs of example 2, Fe-Se-3@N-CNTs of example 3, and RuO2 catalyst;

[0033] Figure 8 The current density is 10 mA cm -2 Below is the cycling performance diagram of the zinc-air battery assembled with the Fe-Se-2@N-CNTs catalyst of Example 2. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0035] The following experimental methods and detection methods, unless otherwise specified, are conventional methods; the following reagents and raw materials, unless otherwise specified, are commercially available.

[0036] The preparation principle of the Fe-Se@N-CNTs catalyst of the present invention is as follows: melamine-assisted pyrolysis of an iron-based MOF material (Fe-BTC) is performed, in the presence of melamine, melamine is used as a nitrogen source and a carbon source, and iron ions are used as catalytic sites for the growth of nitrogen-doped carbon nanotubes (N-CNTs). During the pyrolysis process, the reduction coordination bonds generated between the iron ions and the organic ligands in the Fe-BTC are first broken due to the long binding length, and reducing gases (such as NH3 and H2) are released at the same time. Then, these gases reduce the iron metal ions to metals, promote the nucleation of metal nanocatalysts, and catalyze organic residual units to N-CNTs to obtain Fe3C@N-CNTs catalysts. Finally, the Fe3C@N-CNTs catalysts are mixed with selenium and subjected to selenization reaction to obtain carbon-coated iron selenide bifunctional catalysts supported by nitrogen-doped carbon nanotubes.

[0037] The following examples and comparative examples are used to further study the technical solution of the present invention. The specific research methods and results are as follows:

[0038] Example 1

[0039] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0040] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution. H3BTC has a low solubility in water, so it is dissolved in a sodium hydroxide solution. On the one hand, it is completely dissolved, and on the other hand, the pH value of the solution is adjusted. Here, the pH value affects the preparation of MOF, and a colorless solution A (pH = 10.9) is generated.

[0041] Dissolve 0.508 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B (pH = 1.8);

[0042] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 12 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0043] S2, the Fe-BTC precursor of step S1 and melamine powder are ground and mixed in a mass ratio of 1:1 to obtain a mixture, and then the mixture is placed in a tube furnace under a protective atmosphere of high-purity nitrogen, heated to 500°C at a heating rate of 2°C / min and maintained for 3 hours, then continued to heat to 800°C for pyrolysis for 2 hours, and the cooling rate is controlled to be 10°C / min. After cooling to room temperature, the collected black powder is Fe3C@N-CNTs catalyst;

[0044] S3. The Fe3C@N-CNTs catalyst of step S2 is mixed with selenium powder in a mass ratio of 1:1, and then placed in a tubular furnace. Under an argon protective atmosphere, the mixture is reacted at 450°C for 2 hours. After the temperature is cooled to room temperature, a black powder is collected, which is a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, recorded as Fe-Se-1@N-CNTs catalyst.

[0045] Example 2

[0046] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0047] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution to generate a colorless solution A (pH = 10.9);

[0048] Dissolve 0.508 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B (pH = 1.8);

[0049] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 12 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0050] S2, the Fe-BTC precursor of step S1 and melamine powder are ground and mixed in a mass ratio of 1:1 to obtain a mixture, and then the mixture is placed in a tube furnace under a protective atmosphere of high-purity nitrogen, heated to 500°C at a heating rate of 2°C / min and maintained for 3 hours, then continued to heat to 800°C for pyrolysis for 2 hours, and the cooling rate is controlled to be 10°C / min. After cooling to room temperature, the collected black powder is Fe3C@N-CNTs catalyst;

[0051] S3. The Fe3C@N-CNTs catalyst of step S2 is mixed with selenium powder in a mass ratio of 1:2, and then placed in a tubular furnace. Under an argon protective atmosphere, the mixture is reacted at 450°C for 2 hours. After the temperature is cooled to room temperature, the obtained black powder is collected, which is a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, recorded as Fe-Se-2@N-CNTs catalyst.

[0052] Example 3

[0053] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0054] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution to generate a colorless solution A (pH = 10.9);

[0055] Dissolve 0.508 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B (pH = 1.8);

[0056] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 12 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0057] S2, the Fe-BTC precursor of step S1 and melamine powder are ground and mixed in a mass ratio of 1:1 to obtain a mixture, and then the mixture is placed in a tube furnace under a protective atmosphere of high-purity nitrogen, heated to 500°C at a heating rate of 2°C / min and maintained for 3 hours, then continued to heat to 800°C for pyrolysis for 2 hours, and the cooling rate is controlled to be 10°C / min. After cooling to room temperature, the collected black powder is Fe3C@N-CNTs catalyst;

[0058] S3. The Fe3C@N-CNTs catalyst of step S2 is mixed with selenium powder in a mass ratio of 1:3, and then placed in a tubular furnace. Under an argon protective atmosphere, the mixture is reacted at 450°C for 2 hours. After the temperature is cooled to room temperature, the obtained black powder is collected, which is a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, recorded as Fe-Se-3@N-CNTs catalyst.

[0059] Example 4

[0060] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0061] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution. H3BTC has a low solubility in water, so it is dissolved in a sodium hydroxide solution. On the one hand, it is completely dissolved, and on the other hand, the pH value of the solution is adjusted. Here, the pH value affects the preparation of MOF, and a colorless solution A (pH = 10.9) is generated.

[0062] Dissolve 0.0675 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B;

[0063] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 18 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0064] S2, grinding and mixing the Fe-BTC precursor of step S1 and melamine powder in a mass ratio of 1:2 to obtain a mixture, and then placing the mixture in a tube furnace under a protective atmosphere of high-purity nitrogen, heating it to 450°C at a heating rate of 2°C / min and maintaining it for 4 hours, then continuing to heat it to 1000°C for pyrolysis for 1 hour, controlling the cooling rate to 10°C / min, and cooling the temperature to room temperature. The collected black powder is the Fe3C@N-CNTs catalyst;

[0065] S3. The Fe3C@N-CNTs catalyst of step S2 is mixed with selenium powder in a mass ratio of 0.2:1, and then placed in a tubular furnace. Under an argon protective atmosphere, the mixture is reacted at 500°C for 1 hour. After the temperature is cooled to room temperature, a black powder is collected, which is a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes.

[0066] Example 5

[0067] The preparation method of the carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes comprises the following steps:

[0068] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution to generate a colorless solution A (pH = 10.9);

[0069] Dissolve 0.3375 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B;

[0070] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 12 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0071] S2, the Fe-BTC precursor of step S1 and melamine powder are ground and mixed in a mass ratio of 1:3 to obtain a mixture, and then the mixture is placed in a tube furnace under a protective atmosphere of high-purity nitrogen, heated to 550°C at a heating rate of 2°C / min and maintained for 2 hours, and then continued to heat to 700°C for pyrolysis for 3 hours, and the cooling rate is controlled to be 10°C / min. After cooling to room temperature, the collected black powder is Fe3C@N-CNTs catalyst;

[0072] S3. The Fe3C@N-CNTs catalyst of step S2 is mixed with selenium powder in a mass ratio of 0.5:1, and then placed in a tubular furnace. Under an argon protective atmosphere, the mixture is reacted at 300°C for 3 hours. After the temperature is cooled to room temperature, a black powder is collected, which is a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes.

[0073] Comparative Example 1

[0074] The method for preparing nitrogen-doped carbon nanotube-supported iron carbide nanoparticles is the same as the preparation steps of Example 1, except that step S3 is not performed, and includes the following steps:

[0075] S1. Dissolve 0.263 g of trimesic acid (H3BTC) in 10 mL of 1 mol / L NaOH aqueous solution to generate a colorless solution A (pH = 10.9);

[0076] Dissolve 0.508 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare an orange-yellow solution B (pH = 1.8);

[0077] Solution B was added dropwise into solution A under magnetic stirring to obtain a suspension, the suspension was further stirred at room temperature for 12 hours, and then a solid was obtained by centrifugation. The solid was washed three times with deionized water and ethanol, and dried in vacuo at room temperature. The obtained solid powder was an iron-based covalent organic framework (Fe-BTC) precursor.

[0078] S2. Grind and mix the Fe-BTC precursor of step S1 and melamine powder in a mass ratio of 1:1 to obtain a mixture, and then place the mixture in a tube furnace under a protective atmosphere of high-purity nitrogen, heat it to 500°C at a heating rate of 2°C / min and keep it for 3 hours, then continue to heat it to 800°C for pyrolysis for 2 hours, control the cooling rate to 10°C / min and cool it to room temperature, and the collected black powder is Fe3C@N-CNTs catalyst.

[0079] Examples 1-5 of the present invention all prepared nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalysts with excellent OER and ORR catalytic performance. The Fe-Se@N-CNTs catalysts of Examples 1-3 of the present invention are taken as examples and compared with the Fe3C@N-CNTs catalyst of Comparative Example 1. The specific research methods and results are as follows:

[0080] Figure 1 The figure is a schematic diagram of the preparation of Fe3C@N-CNTs and Fe-Se@N-CNTs catalysts. Usually, the Fe-BTC precursor is synthesized by self-assembly of iron salt and trimesic acid in water at room temperature. In the presence of melamine, melamine serves as a nitrogen source and a carbon source, and iron ions serve as catalytic sites for the growth of nitrogen-doped carbon nanotubes (N-CNTs). During the pyrolysis process, the reduction coordination bonds between the iron ions and the organic ligands in Fe-BTC are first broken due to the long binding length, and reducing gases (such as NH3 and H2) are released at the same time. These gases then reduce the iron metal ions to metals, promote the nucleation of metal nanocatalysts, and catalyze the organic residual units into N-CNTs. After complete pyrolysis, the Fe3C@N-CNTs catalyst is successfully synthesized. Finally, the obtained Fe3C@N-CNTs are mixed with selenium powder and selenized at 450°C to form the Fe-Se@N-CNTs catalyst. The method of the present invention was also used to successfully synthesize Fe-Se@N-CNTs catalysts with different iron-selenium mass ratios (such as 1:1, 1:2 and 1:3) of Examples 1-3, which were respectively called Fe-Se-1@N-CNTs, Fe-Se-2@N-CNTs and Fe-Se-3@N-CNTs.

[0081] Figure 2 (a) The results show that the Fe3C@N-CNTs catalyst is composed of a hollow N-CNTs nanotube conductive network and Fe3C nanoparticles randomly distributed on the surface, and the Fe3C nanoparticles are denoted as Fe3C NPs. Figure 2 (b) The results show that the average diameter of Fe3C NPs is about 20 nm and they are coated with a thin layer (about 2 nm) of amorphous carbon. Figure 2The high-resolution transmission image of (c) shows that the lattice spacing of the Fe3C@N-CNTs catalyst is approximately 0.213 nm, which is consistent with the (211) crystal plane of Fe3C.

[0082] Figure 3 (a)-(b) The results show that the carbon shell in the Fe-Se@N-CNTs catalyst is thicker (about 4nm) and the lattice spacing is 0.34nm compared with that of Fe3C@N-CNTs, showing a highly ordered graphitic carbon morphology. It is worth noting that no aggregation of Fe3C NPs and FeSe2NPs (FeSe2 nanoparticles) was observed during carbonization and selenization, which means that carbon-coated Fe-Se@N-CNTs can prevent the aggregation of FeSe2NPs, thereby improving the stability of the catalyst and expanding the contact area between the active sites and the electrolyte. Figure 3 (c) The results show that the inner core of FeSe2NPs shows a lattice spacing of about 0.256nm, which is consistent with the (111) plane of FeSe2, indicating that iron carbide is converted into iron selenide after selenization.

[0083] Figure 4 The results show that in the Fe3C@N-CNTs catalyst, the sharp peak at ~26° is attributed to the (002) crystal plane of the graphite carbon layer; the peaks at 37.6°, 40.6°, 42.9°, 44.6°, 44.9° and 49.1° are attributed to the (210), (201), (211), (220), (031) and (221) crystal planes of Fe3C, respectively. In the Fe-Se@N-CNTs catalyst, new diffraction peaks appeared at 24.1°, 31.1°, 34.9°, 36.3°, 37.4°, 48.2°, 54.2°, 57.6°, 59.9° and 64.1°, corresponding to the (110), (011), (101), (111), (120), (211) and (221) planes of FeSe2, respectively (JCPDS No. 21-0432).

[0084] Figure 5 The results show that the Fe-Se@N-CNTs catalyst has a -1 and 276.2cm -1 Two weak signal peaks appear at the 20°, corresponding to the Se-Se stretching mode of iron selenide, further confirming the existence of FeSe2 phase in the catalyst. Compared with the Fe3C@N-CNTs catalyst, the intensity ratio of the D peak to the G peak of the Fe-Se@N-CNTs catalyst (I D / I G ) is higher, indicating that the degree of graphitization after selenization is higher. D / IG The value is the lowest, which is 1.02, which may be because its carbon layer is highly graphitized with fewer defects.

[0085] Working electrode preparation:

[0086] Weigh 10 mg of catalyst sample, 500 μL of ethanol, and 25 μL of Nafion binder into a bullet-shaped centrifuge tube, shake evenly and ultrasonicate for 30 minutes to prepare a catalyst suspension; then use a pipette to take the catalyst suspension and apply it to the middle ring of the polished glassy carbon electrode, drip 3 μL at a time, drip twice, a total of 6 μL, and after drying naturally, you can get a working electrode loaded with catalyst;

[0087] The ORR activity test method is as follows: assemble a three-electrode system, use Ag / AgCl electrode as reference electrode, platinum mesh as counter electrode, and glassy carbon electrode loaded with nitrogen-doped carbon nanotube-loaded carbon-coated iron selenide bifunctional catalyst as working electrode, then use linear voltammetry (LSV) on an electrochemical workstation to test its ORR catalytic activity, obtain the catalyst's half-wave potential and limiting current density parameters from the LSV curve, and compare them with commercial Pt / C catalysts to determine their activity. The more positive the half-wave potential, the greater the limiting current density, and the better the ORR activity. Figure 6 The results show that the Fe-Se-2@N-CNTs catalyst exhibits superior ORR activity compared to other catalysts. Moreover, it is comparable to the state-of-the-art Pt / C catalyst (0.86 V and 5.1 mA cm -2 ) compared with the half-wave potential (E 1 / 2 ) is corrected (about 0.88V), and the limiting current density is larger (5.4mAcm -2 ).

[0088] The OER activity test method is the same as the ORR activity test method, except that the potential window and other conditions and judgment criteria during the test are different. OER is obtained from the LSV curve of the catalyst material at a current density of 10 mA cm -2 The overpotential at that time (the voltage minus the water decomposition potential of 1.23V is the overpotential or overpotential) was calculated and compared with the commercial RuO2 catalyst to judge its activity. The lower the overpotential, the stronger the OER activity. Figure 7 The results show that Fe-Se-2@N-CNTs has higher current density and lower overpotential than other catalysts, indicating that it has superior OER activity. Specifically, the Fe-Se-2@N-CNTs catalyst only needs a low overpotential of 360 mV to reach 10 mA cm -2The current density is much lower than that of Fe-Se-1@N-CNTs (440mV), Fe-Se-3@N-CNTs (450mV) and Fe3C@N-CNTs (490mV).

[0089] Figure 8 The results show that the Fe-Se-2@N-CNTs catalyst has a strong effect on ORR (E 1 / 2 =0.88 V) and OER (η = 360 mV @ 10 mA / cm 2 ) have high catalytic activity and good durability. The rechargeable zinc-air battery constructed using Fe-Se-2@N-CNTs cathode has an open circuit voltage of 1.55V and a 2 The peak power density and excellent long-term cycling stability (over 3600 cycles, 1100 h) of the Zn / AlO2 battery were achieved. The present study provides a promising approach for the new design and fabrication of efficient FeSe electrocatalysts for high-performance rechargeable Zn / Air batteries.

[0090] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes, characterized in that: The steps include: Using soluble iron salt and trimesic acid as raw materials, an iron-based covalent organic framework is generated through wet chemical reaction at room temperature; The iron-based covalent organic framework is mixed with melamine, and melamine is used as a nitrogen source, and trimesic acid and melamine are used as carbon sources. The melamine is first decomposed in a protective atmosphere, and then pyrolyzed. The pyrolysis is performed at a high temperature of 700-1000° C. for 1-3 hours. The small molecules of the melamine decomposed during the pyrolysis form carbon nanotubes under the catalysis of iron, and the iron oxide reacts with the carbon source to form iron carbide, thereby obtaining iron carbide nanoparticles supported by nitrogen-doped carbon nanotubes. The iron carbide nanoparticles supported by nitrogen-doped carbon nanotubes are mixed with selenium powder, and then a selenization reaction is carried out to obtain a carbon-coated iron selenide bifunctional catalyst supported by nitrogen-doped carbon nanotubes.

2. The method for preparing the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 1, characterized in that: The mass ratio of the iron-based covalent organic framework to melamine is 1:1-3.

3. The method for preparing the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 1, characterized in that: The conditions of the selenization reaction are as follows: in an inert atmosphere, the iron carbide nanoparticles supported by the nitrogen-doped carbon nanotubes are mixed with selenium powder, and then reacted at 300-500° C. for 1-3 hours.

4. The method for preparing the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 1, characterized in that: The molar ratio of the soluble iron salt to trimesic acid is 0.2-1.5:

1.

5. The method for preparing the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 1, characterized in that: The wet chemical reaction method is as follows: dissolving trimesic acid in a NaOH solution to obtain a solution A; Dissolve a soluble iron salt in water to obtain solution B; Solution B was added dropwise to solution A, and the mixture was stirred until an iron-based covalent organic metal framework was formed.

6. The method for preparing the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 5, characterized in that: The pH value of solution A is 9-12, and the pH value of solution B is 1-3.

7. A nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst according to claim 7 in the preparation of a cathode catalyst for a zinc-air battery.

9. The use according to claim 8, characterized in that: When nitrogen-doped carbon nanotube-supported carbon-coated iron selenide bifunctional catalyst is used as the cathode catalyst of zinc-air batteries, it promotes both oxygen reduction reaction and oxygen evolution reaction.

Citation Information

Patent Citations

  • Carbon nanotube wrapping Fe3C nanocrystalline, manufacturing method and application thereof

    CN110534754A

  • Iron selenide carbon-based material bifunctional catalyst and preparation method thereof

    CN116237067A

  • Nitrogen-doped carbon / cobaltosic selenide / carbon nanotube composite material and preparation method and application thereof

    CN118099348A